Male injection drug users try new drugs following U.S. deportation to Tijuana, Mexico - Robertson, Angela M. (2011)
BACKGROUND: Among male injection drug users (IDUs) in Tijuana, Mexico, U.S. deportation is associated with HIV transmission. Changing drug use behaviors following deportation, including the use of new drugs, may increase HIV risk but are understudied. We identify correlates of trying new drugs following male IDUs’ most recent U.S. deportation to Mexico. METHODS: In 2010, we recruited 328 deported male IDUs in Tijuana, Mexico. Questionnaires collected retrospective data on drug use and other HIV risk behaviors throughout migratory events. Logistic regression identified correlates of trying new drugs/combinations following their most recent deportations. Informed consent was obtained from all participants. RESULTS: Nearly one in six men (n=52, 16%) tried new drugs following their most recent deportation, including heroin (n=31), methamphetamine (n=5), and heroin/methamphetamine combined (n=17). Trying new drugs following deportation was independently associated with U.S. incarceration (adjusted odds ratio [AOR]= 3.96; 95% confidence interval [C.I.] 1.78, 8.84), increasing numbers of U.S. deportations (AOR=1.11 per deportation; C.I. 1.03, 1.20), feeling sad following deportation (AOR 2.69; C.I. 1.41, 5.14), and perceiving that one’s current lifestyle increases HIV/AIDS risk (AOR 3.91; C.I. 2.05, 7.44). CONCLUSIONS: Trying new drugs following U.S. deportation may be related to the unique contexts and stressors experienced by drug-abusing migrants as they attempt to reestablish their lives in Mexico. Findings imply an unmet need for health and social programs to alleviate pre-and post-deportation stressors faced by undocumented and return migrants in the U.S.-Mexico context.